(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the concept of ideological solidarity tells in detail about the social development of human life, the spiritual development of the idea, and the realization of ideological solidarity. In addition, a philosophical analysis that the period of peoples, peoples of nations, nations and the brutal struggle of countries.